Pharmacologic inhibition of L‐tyrosine degradation ameliorates cerebral dopamine deficiency in murine phenylketonuria (PKU). Issue 5 (3rd February 2014) - Harding, Cary O.; Winn, Shelley R.; Gibson, K. Michael; Arning, Erland; Bottiglieri, Teodoro; Grompe, Markus
Abstract: Monoamine neurotransmitter deficiency has been implicated in the etiology of neuropsychiatric symptoms associated with chronic hyperphenylalaninemia in phenylketonuria (PKU). Two proposed explanations for neurotransmitter deficiency in PKU include first, that chronically elevated blood L‐phenylalanine (Phe) inhibits the transport of L‐tyrosine (Tyr) and L‐tryptophan (Trp), the substrates for dopamine and serotonin synthesis respectively, into brain. In the second hypothesis, elevated Phe competitively inhibits brain tyrosine hydroxylase (TH) and tryptophan hydroxylase (TPH) activities, the rate limiting steps in dopamine and serotonin synthesis. Dietary supplementation with large neutral amino acids (LNAA) including Tyr and Trp has been recommended for individuals with chronically elevated blood Phe in an attempt to restore amino acid and monoamine homeostasis in brain. As a potential alternative treatment approach, we demonstrate that pharmacologic inhibition of Tyr degradation through oral administration of nitisinone (NTBC) yielded sustained increases in blood and brain Tyr, decreased blood and brain Phe, and consequently increased dopamine synthesis in a murine model of PKU. Our results suggest that Phe‐mediated inhibition of TH activity is the likely mechanism of impaired dopamine synthesis in PKU. Pharmacologic inhibition of Tyr degradation may be a promising adjunct therapy for CNS monoamine neurotransmitter deficiency in hyperphenylalaninemic individuals with PKU.